PENGARUH ADANYA PENGUMUMAN PEMENANG INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) TERHADAP KEPERCAYAAN INVESTOR - Suci K., Suramaya (Widya Warta, 2010)
Indonesia Sustainability Reporting Award (ISRA) is an award awarded to companies with good performance on Sustainability Reporting (SR). Sustainability Reporting is related to company’s capability in economic affairs, environment, and social responsibility. It is an effective means to keep  reputation, build a stakeholder’s trust, and increase company’s value for investors. ISRA is expected to give a positive contribution to companies which were awarded ISRA  in order to be trusted by investors. Yet, whether those companies were indeed getting investors’ trust was unknown. The aim of this research was to examine the impact of ISRA awarding on stock price. Here, Paired Sample T-test was applied with abnormal return variable. The result of the research showed that the announcement of ISRA receivers didn't have any significant effect on investors’ trust. In other words, the announcement of ISRA  receivers didn't have information content; hence, it  didn't increase investors’  trust.